Physiological Preparation of Hair Cells from the Sacculus of the American Bullfrog (Rana catesbeiana) - Azimzadeh, Julien B. (J Vis Exp, 2017)
The study of hearing and balance rests upon insights drawn from biophysical studies of model systems. One such model, the sacculus of the American bullfrog, has become a mainstay of auditory and vestibular research. Studies of this organ have revealed how sensory cells hair can actively detect signals from the environment. Because of these studies, we now better understand the mechanical gating and localization of a hair cell's transduction channels, calcium's role in mechanical adaptation, and the identity of hair cell currents. This highly accessible organ continues to provide insight into the workings of hair cells. Here we describe the preparation of the bullfrog's sacculus for biophysical studies on its hair cells. We include the complete dissection procedure and provide specific protocols for the preparation of the sacculus in specific contexts. We additionally include representative results using this preparation, including the calculation of a hair bundle's instantaneous force-displacement relation and measurement of a bundle's spontaneous oscillation.